Validity, reliability, minimal detectable change, and methodological considerations for HHD and portable fixed frame isometric hip and groin strength testing: A comparison of unilateral and bilateral testing methods. (September 2022) - Dunne, Cian; Callaway, Andrew J.; Thurston, Joanna; Williams, Jonathan M.
Abstract: Objectives: Comparative assessment of bilateral (KangaTech) and unilateral (HHD) testing modalities through concurrent validity and test-retest reliability. Methodological considerations explored include minimum repetitions and comparison of average and maximum values. Design: Experimental, observational. Setting: Biomechanics laboratory. Participants: Thirty-three participants. Main outcome measures: Concurrent validity using peak force. Test-retest reliability used Abduction and Adduction using 2 trials, randomised between devices. Maximum peak force and average of both trials were used. Results: HHD and KT360 are concurrently valid (r = 0.996); with no significant difference (z = −0.681). Excellent HHD reliability (ICC:0.92–0.96) and KT360 (ICC:0.89–0.97). Significant difference between max peak force and average peak force but within the calculated MDC(%). No significant differences between max peak force between trials. Spearman-Brown prophecy predicted excellent reliability for one trial (ICC:0.81–0.95). Bilateral facilitation was demonstrated using the KT360 with 94.6–101.2% increase in force compared to HHD. Conclusions: With no significant difference between first and second max effort, and excellent prophesised reliability, one rep max effort should be acceptable to use. Body positioning within the KT360 seems to elicit bilateral facilitation rather than deficit, therefore unilateral and bilateral force values are not interchangeable. Highlights: Fixed frame isometric sensors and HHD are concurrently valid. HHD and KangaTech are both reliable devices to use. KangaTech seems to elicite bilateral facilitation, force values not interchangeable. Average and Max force values are not interchangeable. We suggest a one rep max effort should be acceptable to use.